Putting weeds to work - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
In eastern Africa Tithonia diversifolia, a common roadside weed with a beautiful yellow flower, may come into its own in one of the latest agroforestry systems being developed to improve soil fertility. The use of leguminous plants to increase soil...